Television Drama in Spain and Latin America : Genre and Format Translation - Julian Smith, Paul (Institute of Modern Languages Research, 2020)
Television Drama in Spain and Latin America addresses two major topics within current cultural, media, and television studies: the question of fictional genres and that of transnational circulation. While much research has been carried out on both TV formats and remakes in the English-speaking world, almost nothing has been published on the huge and dynamic Spanish-speaking sector. This book discusses and analyses series since 2000 from Spain (in both Spanish and Catalan), Mexico, Venezuela, and (to a lesser extent) the US, employing both empirical research on production and distribution and textual analysis of content. The three genres examined are horror, biographical series, and sports-themed dramas; the three examples of format remakes are of a period mystery (Spain, Mexico), a romantic comedy (Venezuela, US), and a historical epic (Catalonia, Spain). Paul Julian Smith is Distinguished Professor at the Graduate Center, City University of New York. He was previously Professor of Spanish at the University of Cambridge. He is the author of twenty books and one hundred academic articles.
Accepted: 2022-06-02T04:31:38Z Journal Abbreviation: Genre and Format Translation
Keywords: 1-TV; 2-Analyses formalistes; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Espagne (corpus analysé); Mexique (corpus analysé); Venezuela (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

Dramatized Societies: Quality Television in Spain and Mexico - Smith, Paul Julian (Liverpool University Press, 2016)
Over the last decade Spain and Mexico have both produced an extraordinary wealth of television drama. Drawing on both national practices of production and reception and international theories of textual analysis this book offers the first study of contemporary quality TV drama in two countries where television has displaced cinema as the creative medium that shapes the national narrative. As dramatized societies, Spain and Mexico are thus at once reflected and refracted by the new series on the small screen.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); Espagne (corpus analysé); Mexique (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Debating Women’s Issues on Turkish Television: Exploring the Role of Political Power in Women’s Talk - Özcan, Esra (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In this contribution, I provide an in-depth rhetorical and textual analysis of a television debate program broadcast in 2015 on the mainstream television news channel, Habertürk TV in Turkey. The debate brought together women committed to varying political projects, including Kemalism, Islamism, leftist movements, Kurdish women’s movements, and feminism. I find this debate program unique because it took place at a crucial moment in Turkey’s recent history, preceding increasing restrictions on the media that eventually cost more than half of the program participants’ jobs and positions. In my analysis, I focus on how the program’s moderator and the women participants define “women’s issues” in an increasingly authoritarian and conflictual political climate where women are divided with regard to supporting or opposing the Justice and Development Party’s (Adalet ve Kalkınma Partisi—AKP) political program. The results of my analysis show that “sisterhood” does not provide common ground for women in a politically polarized environment and women with more political power dominate the conservation.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Introduction: Turkey’s National Television in Transnational Context - Kaptan, Yeşim; Algan, Ece (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The Turkish television industry has undergone great transformation during the past three decades and enjoyed unprecedented success among national and transnational audiences alike. This chapter reconsiders the rise of Turkish television as a global player and an emerging national industry from a new theoretical perspective by situating Turkish television within the contemporary global developments of international television markets and within its own national history, economic, political, and cultural dynamics. By providing different examples of key turning points in its history, we offer a brief overview of TV production, distribution, and reception in Turkey since the beginning of the industry. We also illustrate how societal debates around television content, such as Turkish TV dramas (dizis), have ignited the question of representation and caused a struggle over official narratives, resulting in the entwining of the industry and production processes with politics. In our introductory chapter, we argue that with the increasing demand for content and the expansion of access to online TV platforms, emerging TV industries play an intricate and complex role in reshaping global television flows. Therefore, the case of the Turkish TV industry constitutes a significant example for understanding the current structural transformations in global television and sheds light on the interplay between national and transnational production, distribution, and reception processes.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

‘Calling Out Around the World’: The Global Appeal of Reality Dance Formats - Heller, Dana (Global Television Formats: Understanding Television Across Borders, 2012)
In this chapter, I would like to consider how interactive reality television contributes to the negotiation between national particulars and transnational media ﬂows. Speciﬁcally, I want to look at the successful franchise So You Think You Can Dance , a dynamic global media ﬂashpoint and a remarkably adaptable format that serves as a site of pleasurable and contradictory engagement with the sense of national culture and community that television manufactures. But what makes the show of particular interest to me is that it allows audiences, in an increasing number of television markets around the world, to collectively determine their ideal national performers through a competition that requires mastery of a virtual international smorgasbord of popular dance forms and styles, the vast majority of which originate elsewhere, or from within the national, racial, and ethnic cultures of others. Second, in choosing to examine dance shows, I join with a growing number of scholars who have, over the past 15 years, argued for increased attention to dance as a primary site of knowledge production concerning bodies, identities, and representation.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; Israël (corpus analysé); Proche-Orient (corpus analysé); Turquie (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)

McTV: Understanding the Global Popularity of Television Formats - Waisbord, Silvio (Television & New Media, 2004)
Globalization has intensified interconnectivity among television industries worldwide. Interconnectivity happens through structural and institutional linkages among television systems and industries worldwide, resulting in an increasingly integrated global business governed by similar practices and goals. The dynamics are reflected in the popularity of television formats. On the surface, global dissemination of formats may suggest not only the global integration of the economy of the industry but also the standardization of content. A dozen media companies are able to do business worldwide by selling the same idea, and audiences seem to be watching national variations of the same show. At a deeper level, however, formats attest to the fact that television still remains tied to local and national cultures. Bringing up examples of Latin American cases, this article argues that television is simultaneously global and national, shaped by the globalization of media economics and the pull of local and national cultures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; Argentine (corpus analysé); Brésil (corpus analysé); Mexique (corpus analysé); Royaume-Uni (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)